The Marshlands of Southern Iraq: a very humanitarian dilemma - Nadeem A Kazmi, Sayyed (2000)
The issue of the Marshlands and their inhabitants - human, animal and plant - encapsulates many divergent themes: scientific, economic, political, cultural and legal. And contrary to most analyses it covers a relatively wide geographical area outside Iraq. But whatever the theme we propose to follow - and in whatever context we wish to pursue a given topic - the common denominator in most discussions surrounding this issue is the environmental destruction of the Marshlands, with the Government of Iraq being accused of a systematic policy that has proved catastrophic both for Iraq's people and their unique natural surroundings, as well as Iraq's neighbours. In the latter context, activities in the Marshes have had perhaps the profoundest effect on the Islamic Repubic of Iran. (Párrafo extraído del texto a modo de resumen)